2018
DOI: 10.1080/15476286.2018.1462655
|View full text |Cite
|
Sign up to set email alerts
|

Primary transcriptome analysis reveals importance of IS elements for the shaping of the transcriptional landscape ofBordetella pertussis

Abstract: Bordetella pertussis is the causative agent of whooping cough, a respiratory disease still considered as a major public health threat and for which recent re-emergence has been observed. Constant reshuffling of Bordetella pertussis genome organization was observed during evolution. These rearrangements are essentially mediated by Insertion Sequences (IS), a mobile genetic elements present in more than 230 copies in the genome, which are supposed to be one of the driving forces enabling the pathogen to escape f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 66 publications
5
62
0
Order By: Relevance
“…Of the 1,543 TTS detected, 14.4% (222 TTS) of them were located in a gene on the opposite strand, thus resulting in antisense RNAs. Up to 75% of all genes were found to be associated with antisense RNAs in bacteria (39)(40)(41). Studies with archaea painted a similar picture (21,42).…”
Section: Secondary Structures Involved In Terminationmentioning
confidence: 89%
“…Of the 1,543 TTS detected, 14.4% (222 TTS) of them were located in a gene on the opposite strand, thus resulting in antisense RNAs. Up to 75% of all genes were found to be associated with antisense RNAs in bacteria (39)(40)(41). Studies with archaea painted a similar picture (21,42).…”
Section: Secondary Structures Involved In Terminationmentioning
confidence: 89%
“…Therefore, for sites with a relative antisense signal less than four times the global deduced antisense shadow, the signal from the less productive strand was ignored. To deduce the global antisense shadow, we applied the same strategy as described in Amman et al (2018) for each chromosome and merged the single values by forming the average weighted by the chromosome length. The observed antisense shadows range between 0.34% and 1.74%.…”
Section: Nascent-seq Data Analysismentioning
confidence: 99%
“…Recently, we applied high-throughput sequencing approaches (RNA-seq and differential RNA-seq) to decipher the transcriptional landscape of B. pertussis (Amman et al 2018). One of the sRNAs discovered by dRNA-seq analysis was identified as an unknown transcript located within the intergenic region between BP2736 and BP2735 genes and originating from the negative strand ( Fig.…”
Section: Identification and Characterization Of The Rgta Srnamentioning
confidence: 99%
“…The extensive impact of the hfq gene deletion on transcriptomic profiles in B. pertussis motivated us to search for regulatory RNAs on a genome-wide scale. A recently determined primary transcriptome of B. pertussis (Amman et al 2018) revealed a large variety of noncoding RNAs, including sRNAs. In this study, we characterize one of the identified sRNAs, which, based on its possible function, was designated RgtA (repressor of glutamate transport).…”
Section: Introductionmentioning
confidence: 99%